Rough Fuzzy Ideals Induced by Set-Valued Homomorphism in Ternary Semigroups. (26th May 2022) - Bashir, Shahida; Aslam, Muhammad; Mazhar, Rabia; Asghar, Junaid
Abstract : The main objective of this paper is to characterize rough approximations of fuzzy ideals in ternary semigroups. Rough fuzzy ideals are used to deal with vague and incomplete information in decision-making problems. In this research, approximations for fuzzy prime ideals in ternary semigroups are studied. It is proved that generalized lower approximations and generalized upper approximations of ∈, ∈ ∨ q -fuzzy prime (resp., semiprime) ideals of ternary semigroups are ∈, ∈ ∨ q -fuzzy prime (resp., semiprime) ideals. For this, the concept of SSVH (strong set-valued homomorphism) and SVH (set-valued homomorphism) is used. Also, it is shown by examples that the lower approximations of fuzzy subsemigroups and fuzzy ideals are not fuzzy subsemigroups and fuzzy ideals, respectively, for SVH.